2020
DOI: 10.21203/rs.3.rs-29778/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socioeconomic Factors Affecting Exclusive Breastfeeding in the First 6 Months of Life

Abstract: Introduction: Despite the numerous emphasis on the importance of exclusive breastfeeding for the first 6 months of life, but studies have indicated that it is low in Iran. In this study, we investigated the economic factors affecting exclusive breastfeeding in the first 6 months of life. Methods: The study population included 6-12 months old children who were referred to Arak healthcare centers with their mothers for vaccination and healthcare. Sampling was performed according to Cochran formula. The questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
2
1
2
Order By: Relevance
“…Different findings were obtained in another study that economic status did not significantly affect exclusive breastfeeding (Winarti et al, 2020). The difference in results with this study was also found in previous studies that socioeconomic factors did not influence exclusive breastfeeding (Nazari et al, 2021).…”
Section: Discussioncontrasting
confidence: 97%
“…Different findings were obtained in another study that economic status did not significantly affect exclusive breastfeeding (Winarti et al, 2020). The difference in results with this study was also found in previous studies that socioeconomic factors did not influence exclusive breastfeeding (Nazari et al, 2021).…”
Section: Discussioncontrasting
confidence: 97%
“…Compared to those who didn’t attend formal education, mothers who attended primary, secondary to preparatory, and college or above education showed higher odds of EBF practice. Elsewhere, primary or higher educational status of mothers was associated with higher odds of breastfeeding up to 6 months of age [ 32 , 38 ]. Mothers with higher educational status might be very likely to have greater exposure to breastfeeding-related information and to translate such information into practice.…”
Section: Discussionmentioning
confidence: 99%
“…Faktor utama adalah kurang pengetahuan dari ibu dan keluarga yang terkait dengan usia, tingkat pendidikan ibu, dan kurang mendapat akses informasi mengenai manfaat ASI dan manajemen laktasi, terutama pada periode antenatal. Selain itu, adanya masalah kesehatan fisik dan psikis ibu serta ibu yang bekerja (Maharlouei et al, 2018;US Department of Health and Human Services, 2011). Masalah kesehatan fisik yang sering menjadi kendala menyusui adalah mastitis atau peradangan pada payudara, ibu menderita penyakit infeksi atau sedang mengkonsumsi obat yang dikhawatirkan membahayakan bagi bayi yang menyusu.…”
Section: Dunclassified
“…Ibu bekerja sering menjadi faktor kegagalan memberi ASI eksklusif. Hal ini karena ketidaktahuan ibu dan keluarga mengenai manajemen laktasi bagi ibu bekerja maupun dukungan lingkungan kerja yang kurang (Maharlouei et al, 2018).…”
Section: Dunclassified